Prepartum change in ventral tail base surface temperature in beef cattle: comparison with vaginal temperature and behavior indices, and effect of ambient temperature - Masafumi MIWA; Shuichi MATSUYAMA; Sho NAKAMURA; Kohei NODA; Miki SAKATANI (The Society for Reproduction and Development, 2019)
Prediction of parturition is essential for sustainable production in beef and dairy cattle, yet the present methods are limited by their high invasiveness and low utility. Here we compared prepartum changes in ventral tail base surface temperature (ST) with changes in vaginal temperature (VT) and behavioral indices. We analyzed 22 parturitions from 22 beef cows. Changes in daily values of ST, VT, and behavioral indices over the 7 days before parturition were investigated. Hourly values were calculated as the actual values minus the mean values for the same hour over a 3-day period, and the changes in hourly values over the 48 h before parturition were investigated. To test the effect of ambient temperature, tested cows were assigned to two season-groups based on the ambient temperature to which they were exposed (warm: n = 13; cool: n = 9), and the daily and hourly values of the indices were compared between seasons. A decrease in ST occurred approximately 30 h before parturition, which was similar to the time of the decrease in VT and earlier than the increase of behavioral indices. In addition, a unique fluctuation of ST observed in the last few hours before parturition indicates that ST could provide a sign for parturition not only in the long-term like VT, but also in the short-term like behavioral indices. Although ST was more sensitive to ambient temperature than VT or the behavioral indices, the day of parturition could be predicted from ST in both the warm and cool seasons.